FACTORS AFFECTING INDONESIAN NATURAL RUBBER EXPORT PRICES - Varwasih, Mia Wananda; Siahaan, Herlyna Nova Sari; Sandra, Indah Kartika (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
The volume and value of Indonesian rubber exports since 2012 have tended to experience a very significant decline due to the decrease in international rubber prices. This decline in international rubber prices then impacts on declining Indonesian rubber export prices. Apart from international rubber prices, other factors are thought to have influenced the export price of natural rubber. Indonesia. The study aimed to analyze the effect of Indonesia's natural rubber export volume, international rubber prices, exchange rates and rubber export prices in the previous period on Indonesia's natural rubber export prices. The data used in this study is 28 year of annual time series data from 1992 to 2019. The results of the survey stated that simultaneously, the independent variables in this study effected on the export price of Indonesian natural rubber, while partially the factors that had a significant effect on the export price of Indonesian natural rubber were the export volume of Indonesian natural rubber, international rubber prices, exchange rates and export prices of rubber in the period before, which means that all the independent variables in this study have a significant effect.